Botulinum toxin A injection to the external urethral sphincter for voiding dysfunction in females: A tertiary center experience. Issue 8 (18th August 2022) - Nadeem, Mehwash; Lindsay, Jamie; Pakzad, Mahreen; Hamid, Rizwan; Ockrim, Jeremy; Greenwell, Tamsin
Abstract: Aim: The aim of this study is to examine the functional outcomes of ona‐botulinum toxin A (BTX‐A) injection into the external urethral sphincter (EUS) for female patients with nonneurogenic nonrelaxing sphincter as the underlying cause of voiding dysfunction (VD). METHOD: A retrospective analysis was performed for all the patients with the urodynamic findings of higher than expected maximum urethral closure pressure (MUCP) who received their first injection during the study period. All patients were evaluated with preoperative videourodynamic study and urethral pressure profilometry and received 100 U of EUS BTX‐A. Patients aged less than 18 years and those with neurogenic bladder were excluded. All patients were followed up with the free flow, postvoid residuals (PVR), and patient global impression of improvement (PGI‐I) scale at 6 weeks and then at 3 monthly intervals. Result: We identified 35 female patients with a mean age of 37.5 ± 15 years (range 18–72 years) with a mean follow‐up of 20 months. More than 50% of patients had a history of prior surgical intervention and 28 (80%) patients were catheter dependent, a suprapubic catheterization, or clean intermittent self‐catheterization. Mean MUCP was 97.1 ± 22 cm of water. After treatment with BTX‐A, 21 (60%) patients were able to void per urethral ( p  = 0.02). The mean maximum flow rate (Qmax) improved from 8.8 to 11 mls/s and the mean PVR decreased from 200 to 149 mls (p  < 0.05 ) . On multivariate analysis, we identified high preoperative PVR, high preoperative actual MUCP, and previous surgical intervention (urethral dilatation, sacral neuromodulation, and pelvic surgery) as predictors of successful voiding restoration. The mean duration of response was 4.7 months, 46% of patients requested repeat injection, and 29% were established on maintenance injections. On the 5‐point PGI‐I score, 13 (37%), 12 (34%), and 10 (29%) patients reported good, some, and no improvement, respectively. Quality of life was also improved in 60% of patients. Two patients had transient stress urinary incontinence (for <6 weeks) and there were no significant long‐lasting adverse events. Conclusion: EUS BTX‐A is a valid treatment option for VD considering therapeutic options are limited. The patient must be made aware of the need for repeat treatments.